A novel contact force model for the impact analysis of structures with coating and its experimental verification. (March 2016) - Cao, Dengqing; Yang, Yang; Chen, Huatao; Wang, Deyou; Jiang, Guangyi; Li, Chenggang; Wei, Jin; Zhao, Kun
Abstract: A novel hysteretic force model is proposed to describe the contact force for the impact analysis of the rotor blade and casing of an aero-engine in this article. Firstly, the structural stiffness of both the flexible blade and casing, as well as the local stiffness of coating painted on both the blade tip and casing are taken into consideration in the formulation of the impact stiffness. Moreover, energy loss during the process of impact is expressed by introducing the nonlinear hysteretic damping. Then, the hysteretic impact force model for both soft and hard coating is obtained. In order to estimate the values of parameters in the contact force model and show the effectiveness of the model, impact experiments are performed at different rotating speeds on a rotor test rig. The impact force and the displacement at the contact point are obtained from the data measured in the experiment. According to the theory of the least square method, the ranges of curvature radius and coefficient of restitution are given respectively. At different rotating speed in certain range, simulation results are compared with the actual experimental results to illustrate the validity and accuracy of the contact force model. Highlights: A novel hysteretic force model is proposed to describe the contact force of the rotor blade and casing. For the rub-impact with hard and soft coatings, the hysteretic contact force model can be simplified to the Kelvin–Voigt model and Lankarani–Nikravesh model, respectively. Impact experiments are performed on the rotor test rig to estimate the values of model parameters and ensure the validity.